First synthesis of nitrosporeusines, alkaloids with multiple biological activities - Philkhana, Satish Chandra; Jachak, Gorakhnath R.; Gunjal, Vidya B.; Dhage, Nagsen M.; Bansode, Ajay H.; Reddy, D. Srinivasa (Tetrahedron Letters, 2015)
Synthesis of nitrosporeusines A and B, thioester-bearing alkaloids from the Arctic Streptomyces nitrosporeus with exceptional biological activity is disclosed for the first time. In addition, we have prepared another biologically important natural product, maleimycin, in optically pure form using a gram-scale enzymatic resolution method. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: Enzymatic resolution; Influenza H1N1 virus; Maleimycin; Michael reaction; Nitrosporeusine